Risk Factors Associated with Children's Behavior in Dental Clinics: A Cross-Sectional Study - Rana Abdullah Alamoudi; Nada Bamashmous; Nuha Hamdi Albeladi; Heba Jafar Sabbagh (MDPI AG, 2024)
One of the most crucial tasks of pediatric dentists is to control children's negative behaviors. This study aimed to assess dental behavior and the associated risk factors among children aged 4-12. This cross-sectional study recruited healthy, unaffected children aged 4 to 12 years. Parents were interviewed regarding the sociodemographic details and characteristics of their children's dental visits. Two collaborative dentists examined the children for dental caries (DMFT/DMFT) and behavioral status (Frankl's behavior rating scale). This study included 439 children: 27.3% exhibited uncooperative behavior, and the mean DMFT/dmft was 8.46 ± 3.530. Uncooperative behavior significantly increased when the dental visit was scheduled as an emergency treatment (p = 0.134; Adjusted Odds Ratio (AOR): 1.530) and when there was an elevated DMFT/DMFT ratio (p < 0.001; AOR: 1.308). This study revealed a significant association between children's uncooperative behavior and their first dental visit, emphasizing the need for tailored strategies to address behavioral challenges when scheduling pediatric dental care. The proactive measures included controlling caries and avoiding emergencies.